Features of the Early Hydrocarbon Accumulation and Its Effects on the Late Accumulation in Sandstone Reservoir: A Case Study of the Eocene Dongying Depression, Bohai Bay Basin - Wang, Miao; Chen, Yong; Song, Guoqi; Liu, Huimin; Wang, Yongshi; Zhang, Pengfei; Qiu, Yibo; Chen, Tao; Li, Jiyan; Liu, Xinjin; Liu, Peng; Feng, Yuelin; et al. (Frontiers in Earth Science, 2022)
Multi-stage hydrocarbon generation and accumulation are very common in petroliferous basins. And determination of hydrocarbon accumulation stages and each related diagenetic features, are important for understanding the distribution of current oil and gas resources in one individual basin. However, few studies have been focused on these resulting features of the first stage of hydrocarbon accumulation and their geological implications in the case of conventional sandstone reservoir. In this study, taking the reservoir from the Eocene Dongying Depression as an example, we investigated the features of the early hydrocarbon accumulation and their effects on the late accumulation, by analyzing of the early accumulation related paragenesis, fluid inclusions, clay minerals content, reservoir physical property and wettability in sandstones. Our results show that the early stage accumulation of the overpressured hydrocarbon fluid could support and offset some loads of overburden, weaken the normal compaction and preserve some original pores. Also, the early hydrocarbon accumulation resulted in an alternated, diagenetic environment from the initial acidic to subsequent alkalic fluid, with the overall dissolution intensity stronger than the cementation, and formed a large number of secondary pores. Therefore, the early accumulation was beneficial to reservoir space development, and provided space for the late hydrocarbons. In addition, the early hydrocarbon accumulation could cause the alteration of rock wettability. During the process of the early accumulation, a lipophilic migration pathway from source rock to reservoir formed gradually. And the late stage of hydrocarbon fluids would preferentially choose this pathway for their migration (i.e., inheritance of migration pathway).